A computational fluid dynamics-based girth welding model for large-diameter pipeline to reveal vertical weld formation mechanism - Yun, Ze; Li, Yan; Wu, Juanhui; Liu, Xiaoben; Wang, Hao; Zhang, Hong (Physics of fluids (1994), 2024)
Welding quality significantly impacts the safety of large-diameter, long-distance pipelines. The molten pool flow, influenced by gravity, results in variations in the girth weld seam at different circumferential orientations. A three-dimensional transient computational fluid dynamics model was developed to study the multi-layer, multi-pass welding process of X80M pipeline, incorporating arc heat, droplet heat, gravity, and fluid flow in the molten pool. The model also simulates dual-torch automatic welding to examine heat transfer and flow characteristics. Notably, it reveals the morphological evolution of the girth weld seam from the 2 to 3 o'clock positions during continuous welding, an area lacking prior research. The results, validated by experiments, show good agreement between the simulation and thermal cycle curves. The weld pool solidifies from the sides toward the center, creating a concave shape due to downward metal flow, with dual-torch welding intensifying this effect. The second torch increases the concavity of filler layers, with depths rising by 21.81% and 32.20%. These findings offer new insights into pipeline girth welding.